Gamelan Gender Wayang Composition “Sandaran Laju” | Komposisi Gamelan Gender Wayang “Sandaran Laju” - I Putu Purwangsa Nagara; I Nyoman Sudiana (Pusat Penerbitan LPPMPP ISI Denpasar, 2021)
Sandaran Laju is a musical artwork inspired by the interest in finding a different timbre from the Gender Wayang gamelan. Sandaran Laju musical form is an experimental piece of music, by making a pattern of the performance by attaching and playing two (2) instruments together so that a different new sound is created from the Gender Wayang gamelan. The meaning of the title Sandaran Laju is to “lean” or